FRI0287 Serologic evidence of viral reactivation and increased disease activity in patients with systemic lupus erythematosus. (12th June 2018) - Wood, R.; Guthridge, L.; Thurmond, E.; Guthridge, C.; Chen, H.; deJager, W.; Macwana, S.; Bourn, R.L.; Kamp, S.; Lu, R.; Arriens, C.; Chakravarty, E.F.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is a clinically heterogeneous disease oftentimes characterised by a waxing and waning disease course. However, mechanisms of disease flare remain elusive. Objectives: This study examined relationships between SLE disease activity, immune pathways, and serologic evidence of viral exposures and reactivation within molecular subsets of SLE patients. Methods: Serial or single samples of plasma, serum and RNA (n=290) were collected from 184 adult SLE patients who met ACR classification and cohort-matched controls (n=49). Disease activity was assessed by modified SELENA-SLEDAI. Immune pathways were evaluated by modular transcriptional analysis of Illumina Beadchip Microarray gene expression data, as well as by plasma soluble mediators (n=32) by multiplex, bead-based assay and ELISAs. This information was used to subset patients into seven molecular-defined categories by random forest modelling. Viral seropositivity and antibody concentrations were detected by ELISA for antibodies against EBV-Viral Capsid Antigen (VCA) (IgG and IgA), EBV-Early Antigen (EA) (IgG), Cytomegalovirus (CMV) (IgG), and Herpes Simplex Virus (HSV-1) (IgG). Results: Serologic evidence of EBV reactivation was more common in SLE patients compared to controls, as measured by antibodies against EBV-EA [IgG] (40% vs 13%; OR=4.57, p=0.0006) or EBV-VCA [IgA] (36% vs 17%; OR=2.70, p=0.019). No differences were noted in CMV or HSV1 seropositivity rates between patients and controls. IgG responses against EBV-VCA were nearly universal among these adult patients and controls; however, concentrations of EBV-VCA IgG were higher in SLE patients compared to controls (ISR=4.44 vs 3.52; p=0.0021), as were EBV-VCA IgA and EBV-EA IgG antibody responses. In cross sectional analysis, SLE patients with higher disease activity (SLEDAI ≥6; n=126) had higher concentrations of EBV-EA IgG than patients with lower (n=166) disease activity (ISR=0.822 vs 0.540; p=0.033). SLE patients with serologic evidence of EBV reactivation by EA IgG responses had higher levels of interferon associated molecules, IP10 (p=3.4×10–1 4 ), BLyS (5.5×10–5), and IL-10 (p=0.00013). HSV1 IgG positive SLE patients also showed higher levels of IP10 (2.2×10–7). Antibody responses toward EBV-EA were enriched in molecularly defined patient clusters with higher expression levels of interferon and inflammatory modules, as well as with interferon and inflammatory soluble mediators. Patients within these clusters were also more likely to have major organ involvement, such as renal or neurologic disease. Conclusions: Serologic evidence of EBV reactivation is more common in SLE patients compared to healthy controls. EBV-EA IgG responses are elevated in SLE patients with active disease and correspond with increases in interferon-associated mediators. This study provides serologic evidence suggesting a possible role for viral reactivation in SLE disease activity. Acknowledgements: This work was supported in part by grants from the National Institutes of Health: U19AI082714, U01AI101934, U54GM104938, P30AR053483, R01AR072401. Disclosure of Interest: None declared